2021
DOI: 10.3390/jcm11010076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity, Smoking, and Sleep on Telomere Length: A Systematic Review of Observational and Intervention Studies

Abstract: Aging is a risk factor for several pathologies, restricting one’s health span, and promoting chronic diseases (e.g., cardiovascular and neurodegenerative diseases), as well as cancer. Telomeres are regions of repetitive DNA located at chromosomal ends. Telomere length has been inversely associated with chronological age and has been considered, for a long time, a good biomarker of aging. Several lifestyle factors have been linked with telomere shortening or maintenance. However, the consistency of results is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 158 publications
(535 reference statements)
1
16
1
Order By: Relevance
“…Certainly, the very modest effect sizes for osteoporotic fracture and arthroplasty suggest little room for therapeutic intervention or indeed for incorporation into risk assessment models. However, given existing evidence linking greater telomere length to healthier diet, lower alcohol intake, and greater physical activity, ( 49 ) all of which are associated with reduced fracture risk, our results provide further evidence to support the role of a healthy lifestyle in older age, ( 50 , 51 ) together with some modest indication of associations between telomere length and fracture/arthroplasty outcomes independent of such considerations.…”
Section: Discussionsupporting
confidence: 68%
“…Certainly, the very modest effect sizes for osteoporotic fracture and arthroplasty suggest little room for therapeutic intervention or indeed for incorporation into risk assessment models. However, given existing evidence linking greater telomere length to healthier diet, lower alcohol intake, and greater physical activity, ( 49 ) all of which are associated with reduced fracture risk, our results provide further evidence to support the role of a healthy lifestyle in older age, ( 50 , 51 ) together with some modest indication of associations between telomere length and fracture/arthroplasty outcomes independent of such considerations.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies on MS have demonstrated that vitamin D insufficiency (21, 22), smoking (23) and higher body mass index (BMI) (24) are associated with increased risk of MS. Moreover, it turns out that vitamin D (25), smoking (26) and BMI ( 27) are also associated with telomere length. Therefore, to make sure the selected SNPs are in accordance with the second core assumption of two-sample MR, we excluded SNPs that are associated with vitamin D traits, smoke status and BMI traits.…”
Section: Genetic Instruments For Telomere Lengthmentioning
confidence: 99%
“…Interventional studies focused on healthy lifestyles (diet, exercise, sleep management, and supplement intake) may slow telomere attrition, improve telomere length maintenance, and increase cognitive functioning (Barragán et al, 2022; Sindi et al, 2017; Yang et al, 2020). Preliminary evidence indicates that meditation and mindfulness interventions aimed at mitigating chronic stress and increasing positive arousal have improved maintenance of telomere length, cognitive function, and psychosocial outcomes.…”
Section: Telomere Attrition and Symptomsmentioning
confidence: 99%
“…Physical activity, function, and symptoms (fatigue, pain, and sleep disturbances) are seen in cancer, cardiovascular, and elderly populations (Alhareeri et al, 2020; Aloni et al, 2021; Barragán et al, 2022; Marques et al, 2020; Sheikh-Wu et al, 2020). Most research in this area investigates the association between telomere length, physical activity, and sleep; however, findings are inconsistent (Alfred et al, 2011; Innes et al, 2018; Ludlow et al, 2013; Ojeda-Rodríguez et al, 2021).…”
Section: Telomere Attrition and Symptomsmentioning
confidence: 99%